2019
DOI: 10.1016/s0140-6736(18)33005-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ten-valent pneumococcal conjugate vaccine on invasive pneumococcal disease and nasopharyngeal carriage in Kenya: a longitudinal surveillance study

Abstract: Summary Background Ten-valent pneumococcal conjugate vaccine (PCV10), delivered at 6, 10, and 14 weeks of age was introduced in Kenya in January, 2011, accompanied by a catch-up campaign in Kilifi County for children aged younger than 5 years. Coverage with at least two PCV10 doses in children aged 2–11 months was 80% in 2011 and 84% in 2016; coverage with at least one dose in children aged 12–59 months was 66% in 2011 and 87% in 2016. We aimed to assess PCV10 effect against nasophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
181
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(193 citation statements)
references
References 38 publications
11
181
1
Order By: Relevance
“…On October 31, 2013, Burkina Faso introduced the 13-valent pneumococcal conjugate vaccine (PCV13) into its routine immunization programme, based on a three-dose schedule at 6, 10, and 14 weeks of age (World Health Organization, 2013). Many studies have reported significant reductions in the burden of pneumococcal disease following the introduction of pneumococcal conjugate vaccines (PCV), including invasive pneumococcal disease (Hammitt et al, 2019) and pneumonia (Silaba et al, 2019;Mackenzie et al, 2017;Grijalva et al, 2007). Given that the protective effects of PCVs may depend on the country-specific context, post-introduction studies have been set up to assess the impact of PCV13 in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…On October 31, 2013, Burkina Faso introduced the 13-valent pneumococcal conjugate vaccine (PCV13) into its routine immunization programme, based on a three-dose schedule at 6, 10, and 14 weeks of age (World Health Organization, 2013). Many studies have reported significant reductions in the burden of pneumococcal disease following the introduction of pneumococcal conjugate vaccines (PCV), including invasive pneumococcal disease (Hammitt et al, 2019) and pneumonia (Silaba et al, 2019;Mackenzie et al, 2017;Grijalva et al, 2007). Given that the protective effects of PCVs may depend on the country-specific context, post-introduction studies have been set up to assess the impact of PCV13 in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…in Sub-Saharan African countries, such as Kenya 17,18 , Malawi 19 , The Gambia 20 and South Africa 21 . In November 2011, Malawi introduced the 13-valent pneumococcal conjugate vaccine (PCV13) as part of the national extended program of immunization with a 3+0 schedule (at 6, 10 and 14 weeks of age).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the fact that radiological pneumonia is more specific for pneumococcal disease. Overall, there was a consistent decline in pneumococcal pneumonia cases in the post-vaccine period in reported impact studies(27,36,42). Two studies that reported on vaccine effect in HIV infected children showed that pneumococcal vaccine had similar impact as with HIV uninfected children(36,41).…”
Section: Discussionmentioning
confidence: 64%
“…One study based pneumonia diagnosis on ICD-10 coding from clinical notes(44). Studies reporting on pneumococcal pneumonia were based on culture with occasional confirmation by Polymerase chain reaction (PCR) (42,45,46) except in one study where PCR based method was used as a means of surveillance(42).…”
Section: Resultsmentioning
confidence: 99%